336 Long-term quality of life of out of hospital cardiac arrest (OHCA) survivors: feasibility of using EQ-5D-3L in an Asian population. (1st May 2022) - Yang, X; Kwan, C; Pek, P; Lim, S; Shahidah, N; Graves, N; Siddiqui, FJ; Liu, N; Ho, A; Ong, M; Investigators, PAROSStudy
Abstract : Background: The purpose of this study was to evaluate the health-related Quality of Life (HRQoL) of OHCA survivors in Singapore using EQ-5D-3L and to assess the factors affecting survey response. Method: Adult OHCA patients aged >/= 18 years between April 2014 to December 2017 who survived to hospital discharge or 30 days were included in a retrospective follow-up study using data obtained from a national registry. EMS-witnessed arrests, those of a drowning or traumatic aetiology, or immediately pronounced dead at scene were excluded. Uncontactable and deceased patients at time of survey were deemed ineligible. The remaining were administered the EQ-5D-3L questionnaire via telephone follow-up at different time points. Results: Of 2727 patients with ROSC, 368 (25%) survived to discharge or were alive at 30 days. At point of survey, 77 (20.9%) had passed away and 38 (10.3%) were uncontactable. Of the remaining 253, 121 (47.8%) refused and interviews were conducted with 132 (52.2% ) patients or proxies. The median follow-up time was 24.5 months (19.2, 33.3) The mean EQ5D index score was 0.77 (SD 0.44), 86 (65.7%) patients had a full score of 1. The mean EQ5D VAS score was 76.3 (SD17.6). Non-responders tended to be older (60.8 vs 54.9, p<0.003), and had poorer neurological status (CPC 3 or 4) (53.7% vs 35.6%, p<0.001). Conclusion: Majority of the OHCA survivors interviewed had a good quality of life post-OHCA at time of follow-up. However, the study was limited by the low response rate, variable follow-up time and selection bias (responders vs non-responders). For future QoL studies, we recommend that follow-up time be standardised after OHCA. Other measurements of HRQoL should be explored in our population. Conflict of interest: No conflict of interests to declare. Funding: None.